The pocket idiot's guide to golf accessories - Mintzer, Richard (Alpha Books, 1999)
This helpful and friendly compact guide shares the in's and out's for all things golf accessories. This book is an ultimate buyer's guide for everything from golf clubs and clothing to golf balls and bags.